DEVELOPMENT OF UMKM THROUGH INSTAGRAM PLATFORM IN BADUNG DISTRICT - Ananda Putra, I Gusti Agung; Tirtayanti, Ni Putu Dila (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The purpose of this service is to develop social media Instagram UMKM Kebaya at the Investment Service and One-Stop Integrated Services. Promotion is part of marketing as a strategy to influence potential customers to have an interest in buying the products or services offered. A good promotion can determine the level of sales of a service or product and is related to customer interest. Badung is a regency located in the province of Bali, Indonesia. The location of the Badung Regency Puspem office is in Sempidi Village, right in the middle of Badung Regency, so it is very strategic as a public service center. There are various agencies in managing the government system including the regent's office, DPRD office, art building, library and official offices, one of which is the One-Stop Investment and Integrated Services Agency (DPMPTSP). In DPMPTSP there are several fields, one of which is the Promotion Field where the author carries out Field Work Practice activities.